1989
DOI: 10.1039/ja9890400483
|View full text |Cite
|
Sign up to set email alerts
|

Precision and accuracy attainable with isotope dilution analysis applied to inductively coupled plasma mass spectrometry: theory and experiments

Abstract: The use of isotope dilution analysis (IDA) in combination with inductively coupled plasma mass spectrometry (ICP-MS) is discussed. In particular, theoretical calculations are presented on the precision and accuracy attainable in the relatively high elemental concentration range. The results of these calculations have been applied to the determination of the amount of Re and Pt on two types of catalysts, with the intention of validating high-precision wet-chemical analysis methods developed for these systems. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Isotope dilution is a powerful method for determining the amount of an element present in a sample using a known amount of an enriched stable isotope as an internal standard. The principles of isotope dilution are well described (73)(74)(75). In reverse isotope dilution, an unknown concentration of an enriched stable isotope is determined by adding a known amount of the unenriched element.…”
Section: Calculations: Amount Of Tracer In a Dosementioning
confidence: 99%
“…Isotope dilution is a powerful method for determining the amount of an element present in a sample using a known amount of an enriched stable isotope as an internal standard. The principles of isotope dilution are well described (73)(74)(75). In reverse isotope dilution, an unknown concentration of an enriched stable isotope is determined by adding a known amount of the unenriched element.…”
Section: Calculations: Amount Of Tracer In a Dosementioning
confidence: 99%
“…However, only the effect of the variance of the dead time was discussed, with no reference to how the dead time should be evaluated. Other authors have focused on attempting to derive a satisfactory method of establishing the detector dead time, with respect to isotope dilution measurements in ICP-MS. A detailed paper by Van Heuzen et al 6 reported the use of calculating the standard deviation about the mean of a set of Re isotope ratio measurements, acquired across a range of Re concentrations, for different dead times, as a means of identifying the optimum dead time. In principle, the optimum dead time will be that for which the standard deviation is at a minimum, since this represents the value for which the different concentration points are scattered evenly about the mean ratio value, without being subject to an upward or downward trend induced by an under or over correction for the dead time effect.…”
Section: Introductionmentioning
confidence: 99%
“…31 Several methods have been developed to determine the dead time (e.g., ref. [35][36][37][38]. Nelms et al (2001) 32 evaluated four methods of dead time calculation on two quadrupole SC-ICP-MS instruments and found that the most suitable method was the one based on studies of the 204 Pb/ 208 Pb isotope ratio measured for a series of Pb solutions with different Pb concentrations.…”
Section: Ion Counter Correctionsmentioning
confidence: 99%